Pengembangan Flipbook Berbasis Augmented Reality (AR) pada Mata Pelajaran IPAS Materi Sistem Gerak Manusia di MIN 20 Aceh Besar - Agustiana, Meli; Fathiah; Islamadina, Raihan; Nurrizqa (Jurnal Elektronika dan Teknologi Informasi, 2025)
Advances in digital technology have had a significant impact on human life, including in the field of education, which has undergone significant changes. Technological advances in education have given rise to various new innovations to support the learning process. Interactive learning media that are in line with current technological developments have a significant impact on learning systems, providing many benefits. However, problems can arise in any school where students feel bored during learning because the learning system is considered to be non-interactive and still uses print media. Therefore, the researcher developed a type of teaching material that can be used by students, namely a learning module for the IPAS subject. One of the digital modules referred to is Flipbook. The use of Flipbook is similar to the use of e-books, but the advantage of Flipbook is that it can be opened page by page like a book and can be accompanied by audio, text, and images, as well as other media such as Augmented Reality (AR). This research uses the ADDIE method, which consists of Analysis, Design, Development, Implementation, and Evaluation, but this research is limited to the Development stage only. Data collection techniques include observation, interviews, and validation tests with media experts and subject matter experts. The platform used to design the Flipbook is Canva, and the 3D Augmented Reality element is created using the Heyzine flipbook.Based on the assessments of media experts and subject matter experts, the results from media experts, namely lecturers and digital classroom teachers in IPAS subjects, were 94%, and the assessments from both subject matter experts, namely IPAS teachers at MIN 20 Aceh Besar were 92%. Therefore, it can be concluded that according to both aspects of the assessment, the Flipbook media is “Highly Suitable” for use by students in classroom learning.